Effectiveness Test of iOptron Cube-G Telescope for Hilal Observation - Firdaus, Muhammad Dimas; Putraga, Hariyadi; Butar-Butar, Arwin Juli Rakhmadi; Hidayat, Muhammad (Universitas Islam Negeri Mataram, 2022)
The use of robotic telescopes in the practice of observing the Hilal in Indonesia is quite widespread. One type of telescope that is widely used by observers is the iOptron Cube. Telescopes with an alt-azimuth mounting type with GPS features can be used easily by observers who observes Hilal on a portable basis. The effectiveness of using this telescope needs to be studied more deeply because pointing accuracy and alt-azimuth tracking mounting capabilities require good computational ability to obtain the expected results. After being tested with two configurations (narrow and wide field of view) and seeing the various supporting features embedded in this telescope, it can be concluded that the iOptron Cube is quite effective for observing Hilal.